2016
DOI: 10.1016/j.jlumin.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt and tunable quenching of photoluminescence in ZnO

Abstract: a b s t r a c tThe abrupt and tunable quenching of photoluminescence (PL) in bulk ZnO samples is reported, a phenomenon which has been previously observed only in GaN and a few phosphorescent materials. ZnO samples grown by the hydrothermal method contain Li defects responsible for the orange luminescence (OL) band with a maximum at 2.0 eV. The Li Zn acceptor is well studied, but there is some disagreement in the literature on the value of its ionization energy. Here we show that the ionization energy of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…The optical properties of Li in ZnO have also been studied extensively. EPR [13,14] and optically detected magnetic resonance studies [9,15,16] have established a correlation between the Li 0 Zn magnetic resonance line and a broad orange luminescence (OL) band with a maximum at 1.95 eV at 10 K [17][18][19]. The OL band is normally present in the photoluminescence (PL) spectrum of hydrothermally (HT) grown ZnO [18] crystals, which contain Li impurities with concentrations in the (1-5) × 10 17 cm −3 range [20].…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of Li in ZnO have also been studied extensively. EPR [13,14] and optically detected magnetic resonance studies [9,15,16] have established a correlation between the Li 0 Zn magnetic resonance line and a broad orange luminescence (OL) band with a maximum at 1.95 eV at 10 K [17][18][19]. The OL band is normally present in the photoluminescence (PL) spectrum of hydrothermally (HT) grown ZnO [18] crystals, which contain Li impurities with concentrations in the (1-5) × 10 17 cm −3 range [20].…”
Section: Introductionmentioning
confidence: 99%
“…Li acceptors give rise to the broad yellow PL band [35], due to the transition of an electron from the conduction band (CB) (or a shallow donor) to the acceptor level. The previous research has demonstrated that there are two processes that lead to yellow PL, excitation from the Liacceptor and excitation from the valence band (VB) [36,37]. The fitted-peak emission line at 627.2 nm corresponds to the RL, the peak-3 could be assigned to the transitions between a shallow donor (at low temperature) or the conduction band (at higher temperature) and the Li zn acceptor [37].…”
Section: Resultsmentioning
confidence: 98%
“…The DLE was composed of the orange luminescence at ~2.1 eV and of the green luminescence at ~2.47 eV. The origin of the orange emission band is generally attributed to different sources such as ionized oxygen interstitials or Li impurities [42][43][44]. The origin of the green luminescence was To prove the conclusions from other characterization techniques, the seed layers preheated at 400 • C and annealed in the air at 600 • C were further investigated by ACOM-TEM (ASTAR) ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The DLE was composed of the orange luminescence at~2.1 eV and of the green luminescence at~2.47 eV. The origin of the orange emission band is generally attributed to different sources such as ionized oxygen interstitials or Li impurities [42][43][44]. The origin of the green luminescence was assigned to the transitions in which oxygen vacancies, oxygen interstitials, or extrinsic defects such as Cu are involved [45,46].…”
Section: Resultsmentioning
confidence: 99%